A post-intentional phenomenological investigation of inclusivity in a therapeutic theatre production. Issue 2 (1st October 2021) - Cook, Angelle
This article presents a dissertation study that investigated the lived experiences of participants engaged in an inclusive therapeutic theatre production through a post-intentional phenomenological lens, informed by critical dis/ability theory. The study included ten participants aged 14‐26 with a variety of dis/abilities. The data were gathered through semi-structured interviews and a focus group and analysed using thematic analysis. The qualitative findings included six themes and fifteen subthemes. These findings suggested that the participants experienced belonging and community, personal growth and insight, feelings of empowerment and the desire to make societal change by being a part of the inclusive production.